PENERIMAAN KELUARGA TERHADAP WARIA ATAU TRANSGENDER (Studi Kasus Atas Waria/Transgender Di Pesantren Waria Al-Fatah Yogyakarta) - Arif Nuh Safri (Nizham Jurnal Studi Keislaman, 2016)
Family is the most urgent aspect of the life of every human being. Since, the family is first community that be obtained by each individual and the first community influencing patterns and lifestyles. Likewise for transgender (waria), the family actually became the basis foundation of their life expectancy. Because a transgender (waria), essentially already experiencing inner conflict since he felt the strangeness or different situations with others. Only, when the inner conflict unfinished openly expressed heard, their courage to open up as a transgender (waria), got the hard rejection. Through this article, the author will give an idea, how the transgender desperately need the presence of family in their lives. In addition, this article also give an understanding of the existence of transgender pesantren (pesantren), and transgender understanding of itself. Thus, expected to open up space for dialogue wider for them.